Florida Crop/Pest Management Profile: Papaya - Mark A. Mossler; Jonathan Crane (EDIS)
Revised! Circular 1402, a 7-page fact sheet by Mark A. Mossler and Jonathan Crane, provides an overview of production and pest management practices for papaya in Florida. Includes references. Published by the UF Department of Horticultural Sciences, November 2009. Reviewed July 2013.